HUBUNGAN USIA IBU HAMIL DENGAN KEJADIAN PREEKLAMPSIA AWITAN LAMBAT DI RUMAH SAKIT UMUM RADEN MATTAHER PROVINSI JAMBI - Rini Mustikasari KP; Silvia Mariana (MIDWIFERY HEALTH JOURNAL, 2019)
Preeclampsia is the leading cause of maternal death in the world. A study estimates that the incidence of preeclampsia in the world ranges from 2% -10% in North America and 5-7 cases per 10,000 births, and in Indonesia Preeclampsia is the cause of 30-40% of perinatal deaths.The purpose of this study was to determine the relationship between the age of pregnant women and the incidence of late onset preeclampsia in Raden Mattaher General Hospital Jambi Province.This study uses a case control design with a Retrospective approach. The population in this study were all pregnant women who performed ANC in Raden Mattaher General Hospital Jambi Province in 2019, with a sample of 108 people consisting of 54 cases and 54 controls. The results of the research that have been done are found in respondents who experience late onset preeclampsia with a risk of maternal age as many as 39 respondents (36.1%) and at risk of maternal age as many as 15 respondents (13.9%), in respondents who did not experience late preeclampsia with the age of at-risk mothers was 23 respondents (21.3%) and the risk of mothers who were not at risk was 31 respondents (28.7%). The results of the chi-square statistical test concluded that there was a relationship between age and the incidence of late onset preeclampsia, with a value (OR) of 3,504 (1,569-7,829), and a p-value of 0,004 was obtained.